2014
DOI: 10.1007/s11655-014-2021-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study on Kangquan Recipe (康泉方) for benign prostatic hyperplasia patients: A randomized controlled trial

Abstract: KQR is effective and safe for the treatment of BPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In this study, Kangquan Recipe (KQR) has a unique effect in treating BPH, with mild effects and small side effects. Clinical studies have shown that [8] KQR can effectively reduce International Prostate Symptom Score (I-PSS) scores, residual urine volume (RUV), and total prostatic volume(TPV) and improve the maximum urinary flow rate (Qmax) and average urine flow rate (Qave) levels in patients with BPH. Previous experimental studies found that [9] the mechanism of KQR treatment of BPH may be to regulate the balance of plasma testosterone and estradiol and reduce the expression of proliferating cell nuclear antigen (PCNA) mRNA to inhibit prostate cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Kangquan Recipe (KQR) has a unique effect in treating BPH, with mild effects and small side effects. Clinical studies have shown that [8] KQR can effectively reduce International Prostate Symptom Score (I-PSS) scores, residual urine volume (RUV), and total prostatic volume(TPV) and improve the maximum urinary flow rate (Qmax) and average urine flow rate (Qave) levels in patients with BPH. Previous experimental studies found that [9] the mechanism of KQR treatment of BPH may be to regulate the balance of plasma testosterone and estradiol and reduce the expression of proliferating cell nuclear antigen (PCNA) mRNA to inhibit prostate cell proliferation.…”
Section: Introductionmentioning
confidence: 99%